An overview of Pakistan´s Textile Sector from operational competitive perspective - A suggestive analysis! - Kazmi, Syeda Asiya Zenab; Takala, Josu (My University, 2014)
The basic aim of this paper is to study and analyze the current level of operational competitive-ness of Pakistani Private Sector—Textile Manufacturing Enterprises. The subject research area will be probed on the basis of making cross reference comparison between the Pakistani Private Sector (PPS)—Textile Manufacturing Enterprises (TME) with the global Textile Manufacturing players in global manufacturing strategies databases. The results revealed that the “quality” is the most important competitive priority of the case PPS-TME and it also pointed towards having some competitive advantages in prospector group. However, it will take considerable amount of time for Pakistani Private Sector—Textile Manufacturing Enterprises to regain their previous global re- cognition and then further improve their operational competitiveness due to the weak and faulty organizational management structure and practices, currently being affected by nation’s political, economic, energy and security situation.
Keywords: Operational Competitiveness; Competitive Edge; Analytical Models; Pakistani Private Sector—Textile Manufacturing Enterprise; Analytic Hierarchy Process; Manufacturing Strategies; Tuotantotalous kauppat.; fi=Tuotantotalous|en=Industrial Management|